PENGEMBANBANGAN MEDIA PEMBELAJARAN POWERPOINT INTERAKTIF PADA TEMA TANAH AIRKU UNTUK ANAK USIA 5-6 TAHUN - Wardana, Mila Anindiya (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2020)
This research was conducted with the aim of producing a valid, appealing, and effective instructional media product in a form of interactive PowerPoint that could help facilitate the learning process for my homeland theme. This study used the ADDIE model which consisted of five main stages, namely the analysis, design, development, implementation, and evaluation stages. The data collection techniques used in this study were interviews and questionnaires. This research shows that the use of interactive PowerPoint instructional media on the theme of my homeland for children aged 5-6 years meets the valid, appealing, and effective criteria and can be used as a tool for teachers or educators in delivering thematic and meaningful learning for children.